Mursi ox modification in the Lower Omo Valley and the interpretation of cattle rock art in Ethiopia. (30th January 2015) - Insoll, Timothy; Clack, Timothy; Rege, Olirege
Abstract: Abstract : Cattle are a key focus of traditional pastoralist societies in eastern Africa and also figure prominently in the rock art of the region. In both contexts, their cultural and social significance is underscored by colour and decoration. The contemporary Mursi of south-west Ethiopia transform favourite oxen in various ways, including horn alteration, ear cutting and decorative pattern branding. These practices may provide direct insight into cattle portrayal in Ethiopian rock art, where abstract or non-realistic symbols depicted on cattle coats could indicate the modification, alteration or beautification of cattle in prehistoric societies.